"Extase". - Popelier, Bert; Hof ter Nederloo, Sint-Pieters-Leeuw; BBL (Bank Brussel Lambert) Brussel (Sint-Pieters-Leeuw : De Vrienden van Nederloo, 1990)
Bouttens, Philippe ; Dacos, Guy ; Lehmann, Manuel Escobar ; Hullebroeck, Amaat ; Leclercq, Guy ; Lenssens, Monika ; Minnaert, Frans ; Monteyne, Roland ; Tanghe, Marijke ; Theys, Yvan ; Vandevyvere, Bart ; Henst, Guy Vander ; Van Herzele, Anne ; Van Langhe, Gisele ; Van Lissum, Paul ; Van Ransbeeck, Agnès
biografie
"Extase", Hof ter Nederloo, Sint-Pieters-Leeuw, 23 maart 1990 - 29 april 1990
Nederlands
boek